Anais Do XXV Simpósio Brasileiro De Informática Na Educação (SBIE 2014) 2014
DOI: 10.5753/cbie.sbie.2014.392
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de uma aplicação web para auxiliar no ensino da Matemática para alunos do Ensino Fundamental

Abstract: Abstract. This paper presents the development of a web application focused for training math concepts in elementary school students. The system allows students solve a series of problems divided according to the classification used by OBMEP, as themes, sub-themes and levels. The application is implemented with Gamification concepts. The problems were selected using a method developed by the authors, described in the article, and had their variables generalized to ensure that the student does not memorize the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Other researchs [Farias et al 2016, Toda et al 2014, da Rocha Seixas et al 2014, Andrade and Canese 2013 introducing similar proposes, indicated the EG's effectivity to stimulate users engagement, presenting positive results. Although the advantages established on the literature, [Boulet 2016] points out that tools which use gamification concepts might suffer from the lack of interest or become annoying, after it is used for a determined period of time.…”
Section: Educational Gamesmentioning
confidence: 95%
“…Other researchs [Farias et al 2016, Toda et al 2014, da Rocha Seixas et al 2014, Andrade and Canese 2013 introducing similar proposes, indicated the EG's effectivity to stimulate users engagement, presenting positive results. Although the advantages established on the literature, [Boulet 2016] points out that tools which use gamification concepts might suffer from the lack of interest or become annoying, after it is used for a determined period of time.…”
Section: Educational Gamesmentioning
confidence: 95%
“…Sabe-se que, por si só, as tecnologias não resolverão todos os problemas da educação brasileira, que também envolve formação de professores, participação familiar, infraestrutura, entre outros. No entanto, são inúmeros os casos em que as Tecnologias Digitais da Informação e Comunicação (TDIC) proporcionam melhorias na forma como o conhecimentoé construído, auxiliando professores, pais e alunos na busca por um aprendizado mais contextualizado [TODA et al, 2014]. Um exemplo de aplicação de TDIC está na utilização de jogos tecnológicos como ferramenta no auxílio ao aprendizado, que pode levarà criação de situações de ensino e aprendizagem motivadoras, dinâmicas e envolventes [CARVALHO et al, 2015].…”
Section: Introductionunclassified
“…Este trabalho visa demonstrar a continuação do desenvolvimento de um sistema web, inicialmente proposto por Toda et al (2014), para auxiliar na transmissão de conceitos da aritmética, com o intuito de contribuir para o ensino da Matemática. O presente trabalho abrange os conteúdos encontrados em problemas de aritmética de alunos do quinto e sexto ano, oriundos do material elaborado pelo comitê acadêmico da OBMEP, além de apresentar um método para classificação e sistematização dessas questões.…”
Section: Introductionunclassified